Factors associated with low health literacy among community-dwelling women in Taiwan. Issue 5 (27th May 2020) - Huang, Chi-Hsien; Talley, Paul C.; Lin, Chi-Wei; Huang, Ru-Yi; Liu, I-Ting; Chiang, I-Hui; Lu, I-Cheng; Lai, Yu-Cheng; Kuo, Kuang-Ming
ABSTRACT: The present study investigated factors associated with health literacy in community-dwelling Taiwanese women, particularly focusing on those associated with prevalent unhealthy behaviors. This cross-sectional study recruited 353 community-dwelling women aged 39–89 years from February to October 2015 in urban, suburban, and rural areas. Variables investigated included physical activity, community activity, tobacco usage, alcohol consumption, and betel-nut chewing. Degree of health literacy was evaluated using the Chinese-language version of the European Health Literacy Survey Questionnaire. Most respondents had inadequate (17.6%), or problematic (49.3%), general health literacy. Multiple logistic regression analyses showed that low educational attainment was closely associated with inadequate or problematic general health literacy. Women who did not engage in regular physical activity or direct community activity were more likely to have inadequate and problematic general health literacy, respectively. Selected unhealthy behaviors (tobacco usage, alcohol consumption, betel-nut chewing) were not associated with health literacy. Low health literacy was prevalent among participants. Lower educational attainment and a lack of physical or community activity were associated with low health literacy. Health literacy should be considered during the process of delivering health information, and health education programs must enhance health literacy tailored to address individuals' lifestyles.